Apple sugar content non-destructive detection device based on near-infrared multi-characteristic wavelength. Issue 1 (1st May 2022) - Liu, Weihui; Han, Yanan; Wang, Na; Zhang, Zhen; Wang, Qingguo; Miao, Yongping
Abstract: Knowing the sugar content of apples in time and grading the internal quality of apples can meet the requirements of different consumers for apples. In this paper, Yantai Red Fuji apples are used as the research object, a low-cost and portable non-destructive testing device for apple sugar content is designed based on near-infrared detection technology. To realize the quantitative detection of apple sugar content, The relationship between the voltage value of diffuse reflection light and the sugar content of apples at multiple characteristic wavelengths is studied, and the multiple linear regression method is used to establish the apple sugar content prediction model. The correlation coefficient predicted by the model is 0.7708, and the minimum relative error is 0.89%. The experimental results show that within a certain error range, the device can realize fast and non-destructive detection of the sugar content of apples. This article provides a reference for the realization of a low-cost, portable non-destructive testing device for Apple.